Pharmacokinetic Interaction of Riociguat with Ketoconazole, Clarithromycin, and Midazolam. (March 2016) - Becker, Corina; Frey, Reiner; Unger, Sigrun; Thomas, Dirk; Reber, Michael; Weimann, Gerrit; Dietrich, Hartmut; Arens, Erich R.; Mück, Wolfgang
Riociguat is a soluble guanylate cyclase stimulator for the treatment of pulmonary hypertension that is principally metabolized via the cytochrome P450 (CYP) pathway. Three studies in healthy males investigated potential pharmacokinetic interactions between riociguat and CYP inhibitors (ketoconazole, clarithromycin, and midazolam). In two studies, subjects were pretreated with either once-daily ketoconazole 400 mg or twice-daily clarithromycin 500 mg for 4 days before cotreatment with either riociguat 0.5 mg ± ketoconazole 400 mg or riociguat 1.0 mg ± clarithromycin 500 mg. In the third study, subjects received riociguat 2.5 mg 3 times daily (tid) for 3 days, followed by cotreatment with riociguat 2.5 mg tid ± midazolam 7.5 mg. Pharmacokinetic parameters, the effect of smoking on riociguat pharmacokinetics, safety, and tolerability were assessed. Pre- and cotreatment with ketoconazole and clarithromycin led to increased riociguat exposure. Pre- and cotreatment with riociguat had no significant effect on midazolam plasma concentrations. In all studies, the bioavailability of riociguat was reduced in smokers because its clearance to the metabolite M1 increased. Riociguat ± ketoconazole, clarithromycin, or midazolam was generally well tolerated. The most common treatment-emergent adverse events (TEAEs) across all studies were headache and dyspepsia. One serious TEAE was reported in the midazolam study. Owing to the potential for hypotension, concomitant use of riociguat with multipathway inhibitors, such as ketoconazole, should be approached with caution. Coadministration of riociguat with strong CYP3A4 inhibitors, for example, clarithromycin, does not require additional dose adjustment. No significant drug-drug interaction was revealed between riociguat and midazolam.